Fixed-removable partial denture - A case report - Sushma, K N; Kumar, Santosh (Indian Journal of Case Reports, 2020)
One of the most common stigmas prevalent in dental practice is quackery. This targets the practice from both the ends: The service provider and patient population. This article reports a case where such a practice permanently damaged the patient’s teeth finally making the patient completely edentulous at an early age and also discusses the various hazards caused by quackery in dentistry.